Pengaruh Alokasi Dana Desa, Pendapatan Asli Desa (PADesa) dan Kebijakan Desa Terhadap Tingkat Kesejahteraan Masyarakat di Desa Ploso Kecamatan Selopuro Kabupaten Blitar - Nila Khoirur Rosyidah; Anik Malikah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of Village Fund Allocation, Village Original Income, and Village Policy on the level of community welfare in Ploso Village, Selopuro District, Blitar Regency. This study uses a type of quantitative research, using primary data obtained from the results of distributing questionnaires and in its measurement using a Likert scale. As for the secondary data, it was obtained from previous research, as well as the profile book of Ploso Village, Selopuro District, Blitar Regency. The population used in this research is the people of Ploso Village which consists of Ploso Hamlet and Kasim Hamlet. For sampling using the slovin formula and obtained a sample of 100 respondents. While in this study, the sampling technique used purposive sampling technique. The data analysis technique used IBM SPSS 25. From this study the results were obtained that: 1) Based on the results of the t test it was found that the Village Fund Allocation and Village Policy variables partially affected the level of community welfare in Ploso Village, Selopuro District, Blitar Regency, 2) Based on the test results t obtained that Village Original Income partially does not affect the level of community welfare in Ploso Village, Selopuro District, Blitar Regency.Keywords : Village fund allocation, village original income, village policy